2019
DOI: 10.1038/s41377-019-0232-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous emission of orthogonal handedness in circular polarization from a single luminophore

Abstract: The direct emission of circularly polarized (CP) light improves the efficiency of an organic light-emitting diode and characterizes the secondary structure of proteins. In most cases, CP light is generated from a luminescent layer containing chiral characteristics, thereby generating only one kind of CP light in an entire device. Here, we propose direct CP light emissions using a twisted achiral conjugate polymer without any chiral dopant as an emitting layer (EML). The twisted structure is induced in the meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…In an effort to rationalise this observation with previously reported results, we introduced anisotropic alignment layers of rubbed polyimide (PI) before spin-coating the polymer thin films. 17,44,45 Rubbed PI layers have been shown to promote the unidirectional alignment of liquid-crystalline materials. 44,46 In contrast to their non-aligned counterparts, the MMSE of polymer thin films with alignment layers have linear and circular terms in both reflection and transmission ( Figure S9), which cannot be isolated upon sample rotation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to rationalise this observation with previously reported results, we introduced anisotropic alignment layers of rubbed polyimide (PI) before spin-coating the polymer thin films. 17,44,45 Rubbed PI layers have been shown to promote the unidirectional alignment of liquid-crystalline materials. 44,46 In contrast to their non-aligned counterparts, the MMSE of polymer thin films with alignment layers have linear and circular terms in both reflection and transmission ( Figure S9), which cannot be isolated upon sample rotation.…”
Section: Resultsmentioning
confidence: 99%
“…17,44,45 Rubbed PI layers have been shown to promote the unidirectional alignment of liquid-crystalline materials. 44,46 In contrast to their non-aligned counterparts, the MMSE of polymer thin films with alignment layers have linear and circular terms in both reflection and transmission ( Figure S9), which cannot be isolated upon sample rotation. For the aligned CSCP films we first attempted to fit these data using an optical model with natural optical activity but found that it could not accurately reproduce both linear and circular terms simultaneously (Figure 4, Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…[30] The simulation is based on the rigorous coupled-wave analysis (RCWA). [33][34][35] The conventional RCWA algorithm is focused on incidence of linearly polarized waves, rather than circularly polarized waves. For an aid of easy understanding of the numerical method, a detailed description of the RCWA is presented in the Appendix for incidence of an arbitrarily polarized wave.…”
Section: Modellingmentioning
confidence: 99%
“…Using RCWA to calculate the reflection and transmission of the grating structures has been discussed by several groups. [33][34][35] Here we would like to give a detailed description about this process for arbitrarily polarized wave in this paper.…”
Section: Appendix the Rcwa For Arbitrarily Polarized Wavementioning
confidence: 99%
See 1 more Smart Citation